Singapore as an incentive travel destination. - Lee, Irene. (2008)
The objective of this research study is to evaluate the importance of various destination-related attributes to an incentive travel destination. The study also aims to analyseSingapore’s performance along the same attributes. This report will uncover Singapore’s strengths and weaknesses as an incentive travel destination and the problems faced by local destination management companies (DMCs).